The significant role of customer brand identification towards brand loyalty development: an empirical study among Malaysian hypermarkets customer - Nikhashemi, Seyed Rajab; Paim, Laily; Osman, Syuhaily; Sidin, Samsinar (Elsevier BV, 2015)
The aim of this study was to identify the significance role of customer brand identification towards building customer brand loyalty via mediating effect of brand trust and word of mouth communication among Malaysian hypermarket customers. A self-administered questionnaire was used to collect data (n=300), using convenience sampling from Mydin, Tesco, Aeon Big, and Giant’s hypermarket customers in metropolitan Kuala Lumpur, Malaysia. Structural Equation Modeling was employed to analyze the data. The result revealed that brand trust and word of mouth communication fully mediate the influence of customer brand identification towards building customer brand loyalty. Moreover, this study identified that the indirect impact of customer brand identification via brand trust and word of mouth communication is more significant than its direct effect.